Comparisons of the anti-inflammatory, antiviral, and hemostatic activities and chemical profiles of raw and charred Schizonepetae Spica. (5th October 2021) - Liu, Xindan; Huang, Zihan; Zhang, Jinju; Zhou, Yu; Zhang, Ying; Wu, Menghua; Ma, Zhiguo; Cao, Hui
Abstract: Ethnopharmacological relevance: A common view in traditional Chinese medicine (TCM) theory is that "processing can alter the efficacy of crude drugs". The clinical usage of some processed products may have already changed greatly over time during the development of modern scientific analysis. Therefore, the view of "processing can alter the efficacy of crude drugs" should be confirmed by comparative studies. Schizonepetae Spica (SS), a Chinese medicinal herb, is the dried spike of Schizonepeta tenuifolia Briq. It is available in two forms: raw products and charred products (Schizonepetae Spica Carbonisata, SSC; raw SS processed by stir-frying until carbonization). Raw SS is commonly used to treat TCM symptoms that resemble common cold, fever, respiratory tract infection and allergic dermatitis, while SSC has long been used as a remedy for TCM symptoms that resemble bloody stool and metrorrhagia. Aim of the study: We aimed to examine whether stir-fry processing alters the anti-inflammatory, antiviral and hemostatic activities of SS and explore the chemical profile behind the potential changes in medicinal properties caused by stir-fry processing. Materials and methods: We used cell models to examine the anti-inflammatory and antiviral effects of raw SS and SSC. The bleeding time of the tail bleeding model and clotting time of the capillary method in mice were used to compare the hemostasis properties of raw SS and SSC. The chemical profiles of SS and SSC were compared using a method combining gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (HPLC/Q-TOF-MS) analysis. Results: The anti-inflammatory effects of SSC were less potent than those of raw SS. Both raw SS and SSC effectively inhibited viral infection in a dose-dependent manner, with IC50 values of 96.30 and 9.73 μg/mL and selectivity index (SI) values of >1.56 and 7.78, respectively. Interestingly, SSC showed more potent antiviral activities than raw SS. Intragastric administration of raw SS and SSC to mice demonstrated that the hemostatic effects of SSC were more potent than those of raw SS. By comparing the volatile chemical profiles of SSC, we found that twenty-nine constituents disappeared and that fifty-four new constituents were formed while the relative contents of five other components decreased and three other components increased. Additionally, the nonvolatile chemical profiles of raw SS and SSC differed, with thirty-two lower peaks and seven higher peaks in SSC than in SS. Conclusion: Our study showed that raw SS and SSC support traditional practice for the clinical applications of these two products except for raw SS used for the treatment of viral infection. It is a fascinating challenge to form SSCs with both traditional hemostatic activities and antiviral properties after stir-fry processing. In addition, the volatile and nonvolatile chemical constituents of raw SS changed dramatically during processing. Further studies are warranted to explore whether the change in chemical constituents is in accordance with the purpose of processing. Graphical abstract: Image 1 Highlights: Validate the impact of traditional stir-fry processing on the efficacy of Schizonepetae Spica (SS). Uncover the chemical basis underlying the potential changes in medicinal properties caused by traditional stir-fry processing of SS. Illustrate the traditional use of raw SS for the treatment of viral infection is less potent than that of Schizonepetae Spica Carbonisata.